Kompetensi Antenatal Care Bidan Alumni Akademi Kebidanan Yogyakarta Di Propinsi Nusa Tenggara Barat - Eka Nur Rahayu (Jurnal Ilmu Kebidanan (Journal of Midwivery Science), 2015)
Background: In 2013 Midwifery Academy Yogyakarta formed a partnership with Ministry of Disadvantaged Areaswith the aim that graduates could be health workers in disadvantaged areas. West Nusa Tenggara still lackingmidwives has set midwives as PTT (civil impermanent servants). This study investigates the Antenatal Care competence of midwives in maternity care.Objective: to know how competence of midwifery academy graduates in providing antenatal care in West NusaTenggara province.Methods: The research method mixed quantitative and qualitative survey using questionnaires and interviews.The population comprised all alumni of Yogyakarta Midwifery Academy from the province of West Nusa Tenggarain Mei- July 2014. The samples were taken by purposive sampling representing alumni working in primary healthcenters, hospitals, and independent practiceResults: The alumni were 62 midwives. Most were working in Polindes or primary health center, having no integrated services mainly for laboratory examination. Midwives working in hospitals do not necessarily provide antenatal care, depending on their ward assignation. Complications or referral services were conducted in accordancewith standard procedures. Length of working experience improves the ability of midwives in the early detection ofcomplications and referral.Conclusions and suggestions: Antenatal care competence was in accordance with procedures. Midwives shouldincrease their knowledge and skills in accordance with the government program.Keywords: midwife competence, antenatal care.